Integrative medicine and health in undergraduate and postgraduate medical education - Hahn, Eckhart Georg (GMS Journal for Medical Education, 2021)
Background and objective: Integrative Medicine and Health (IMH) is a theory-based paradigm shift for health, disease and health care, which can probably only be achieved by supplementing medical roles and competences.
CRIS-Team WoS Importer:2021-03-26